Un château et des chevaux : sauvegarde et valorisation du patrimoine écrit du haras de Pompadour - Gisèle Drigeard; Véronique Latreille de Lavarde (In Situ)
There is an exceptional literary heritage at the national stud farm of Pompadour and Nicole de Blomac, who is a historian and specialist in horses, was well aware of it. So she stepped up initiatives among the directors of stud farms as well as the directorate of national and regional Archives in order to save this heritage from dispersal or deterioration. The authors give here an account of the itinerary of the old archives collection of the estate of Pompadour, from the checking step taken by a young paleographer in 2000 to the pioneering process of handing this collection over to the Archives and sorting it out, and eventually, its promotion through the publication of a digital directory and academic pieces of work.